Factors Related to Antenatal Care Visit in Pregnant Women in The Work Area of Se'i Primary Health Care, Timor Tengah Selatan District - Nida Tasuib; Imelda F. E. Manurung; Ribka Limbu (Universitas Nusa Cendana, 2022)
The coverage of antenatal care (ANC) at Sei Primary Health Care is still low. In 2018, the coverage of the first visit (K1) was 64% and the coverage of the fourth visit (K4) was 45% with 3 cases of maternal mortality. In 2019, K1 coverage was 68% and K4 coverage was 59%. This study aims to analyze the factors related to the ANC behavior in pregnant women in the work area of Sei Health Center, South Central Timor Regency. This type of research was an analytic survey with a cross-sectional design. The population consisted of 181 mothers who gave birth in January - September 2020. The sample of 60 mothers was selected by applying simple random sampling using the Slovin formula to determine the sample size. Data analysis used a chi-square test. The result found that age (p-value=0.033), knowledge (p-value=0.000), family support (p-value = 0.023), socio-cultural (p-value = 0.000), and house distance (p-value=0.041) were associated with ANC behavior. Parity (p-value=0.155) and work (p-value = 0.365) were unrelated to ANC behavior. Health workers in the work area of Sei Health Center (midwife/health promoter) need to increase health education about the importance of antenatal care visits and disseminate the information through leaflets to increase the knowledge of pregnant women.